TEACHER RECRUITMENT MANAGEMENT AT RAUDHATUSSHALIHIN ISLAMIC BOARDING SCHOOL - Rifai, Muhammad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2023)
This research aims to describe the management of teacher recruitment at the Raudhatusshalihin Islamic Boarding School. This type of research uses a qualitative approach with descriptive analytical study methods. Data collection used observation, interview and documentation study methods. Next, the data was analyzed using data reduction techniques, data presentation, and drawing conclusions. To test the validity of the data, data triangulation techniques were used. The results of this research conclude that the management of teacher human resource recruitment at the Raudhatusshalihin Islamic Boarding School is quite good, where the implementation procedures include: planning, announcements, applications, candidate selection, recruitment tests, graduation announcements and appointments. The entire teacher recruitment and selection process at the Raudhatusshalihin Islamic Boarding School has been carried out in accordance with the procedures stipulated in the Employee Work Manual. With this SOP, the recruitment tests carried out are more objective. However, the dissemination of vacancy information through print media and online media is not optimally used, because madrasahs often use it verbally through teachers at the madrasah. At the selection stage, there were still a few problems faced by the recruitment team, namely that some applicants did not fully prepare the files or things they had to bring when applying.